“They Leave Their Babies Where?”: The Case of Repair-Driven Learner Explanation in an Adult ESL Conversation Class - Cicely Rude (Studies in Applied Linguistics & TESOL)
In a world in which rampant misinformation and partial truths can spread like wildfire, adult English as a Second Language (ESL) conversation classes can become fertile ground for unplanned discussions about unexpected information. When a student introduces new information, it can lead to repair-driven side sequences in which student explanations take center stage. These moments not only help clarify misunderstandings but also provide valuable opportunities for learners to strengthen their interactional competence and navigate nuanced communication challenges in the target language.